2005
DOI: 10.1002/aoc.907
|View full text |Cite
|
Sign up to set email alerts
|

Application of electrochemically generated molybdenum-based catalyst system to the ring-opening metathesis polymerization of norbornene and a comparison with the tungsten analogue

Abstract: This study describes the application of the electrochemically generated molybdenum-based catalyst system MoCl 5 -e − -Al-CH 2 Cl 2 to ring-opening metathesis polymerization of bicyclo[2.2.1]hept-2-ene (norbornene). The results are compared with those previously obtained by the WCl 6 -e − -Al-CH 2 Cl 2 system. The polymer product has been characterized by 1 H and 13 C NMR, IR and gelpermeation chromatography techniques. This molybdenum-based catalyst system has led to a mainly trans stereoconfiguration (ca 60%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Before quenching, each polymerization was usually monitored for 99+% conversion via 1 H NMR. The olefinic proton peaks were used to determine the cis : trans ratio via peaks at ∼5.3 and ∼5.5 ppm, respectively, as reported by others. Although in some cases these peaks were unresolved, in others they could be individually integrated and indicated a predominance of trans double bonds, on average 74 ± 6% for polymer series 2 ; this is similar to other reports for polynorbornenes made with Grubbs 1 catalyst …”
Section: Results and Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Before quenching, each polymerization was usually monitored for 99+% conversion via 1 H NMR. The olefinic proton peaks were used to determine the cis : trans ratio via peaks at ∼5.3 and ∼5.5 ppm, respectively, as reported by others. Although in some cases these peaks were unresolved, in others they could be individually integrated and indicated a predominance of trans double bonds, on average 74 ± 6% for polymer series 2 ; this is similar to other reports for polynorbornenes made with Grubbs 1 catalyst …”
Section: Results and Discussionsupporting
confidence: 85%
“…The number-average molecular weights for the polymers were calculated from the 1 H NMR spectra as outlined above and, although generally higher than targeted, were close to the theoretical values. 1 H NMR spectra, via the olefinic signals at 5.45 and 5.26 ppm in a ratio of 3:1, indicated that polymers 5 all had 75% cis linkages.…”
Section: Results and Discussionmentioning
confidence: 97%
“…[3] Several recent studies describe the use of WCl 6 -ē-Al-CH 2 Cl 2 and the MoCl 5 -ē-Al-CH 2 Cl 2 catalyst systems to effect ring-opening metathesis polymerization of norbornene. [17,18] The electrochemical W-based catalyst produces mainly cispolynorbornene (ca. 60%) whereas Mo-based catalyst produces mainly trans-polynorbornene (ca.…”
Section: Introductionmentioning
confidence: 99%
“…60%). [18] In light of our recent carbon arc work that was applied successfully in olefin metathesis reactions, [14] we describe the application of the MoCl 5 -C and WCl 6 -C systems to the ROMP of norbornene.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 We previously reported many scientific studies on the application of WCl 6 -e À -Al-CH 2 Cl 2 catalyst system to olefin metathesis reactions [23][24][25][26][27][28][29] but only one study on MoCl 5 -e À -Al-CH 2 Cl 2 catalyst system to ROMP of norbornene. 30 In this paper we described the synthesis of ROMP of COT with the electrochemically generated W and Mo-based catalyst. The major advantages of these catalyst systems (WCl 6 -e À -Al-CH 2 Cl 2 and MoCl 5 -e À -Al-CH 2 Cl 2 ) electrochemically generated are easily preparation and higher selectivity.…”
mentioning
confidence: 99%